Uji Akurasi Pengukuran Arah Kiblat Masjid Di Kecamatan Panakukang Kota Makassar - Musdalifah, Zahra Ridha Magfirah SR; Maloko, Thahir; Irfan, (HISABUNA: Jurnal Ilmu Falak, 2024)
This study aims to find out how the results of calculating the Qibla direction of the mosque and the accuracy of the Qibla direction of the mosque using the Qibla Tracker, Qibla Arc, and Google Earth instruments. The type of research used is field research which is descriptive qualitative in nature. This study uses an astronomical and syar'i approach. Source of data in this study from primary data and secondary data. Data processing techniques and data analysis in the form of data reduction, data presentation, inference, and verification as well as the final conclusion. The results of the study found that 5 out of the 13 mosques in this study still had an inaccurate Qibla or did not face the true Qibla. Qibla tracker and protractor methods get the same results as the google earth method. The implication of this research is that it is hoped that the local government, especially the KUA, will re-verify the Qibla direction of the mosque in order to correct the deviation that has occurred. In addition, it is necessary to socialize the accuracy of the Qibla direction to the community and provide a basic understanding to the community regarding the importance of the Qibla direction in carrying out worship, as well as the instruments used in determining the Qibla direction. Keywords : Accuracy, Qibla Direction, MosqueThis study aims to find out how the results of calculating the Qibla direction of the mosque and the accuracy of the Qibla direction of the mosque using the Qibla Tracker, Qibla Arc, and Google Earth instruments. The type of research used is field research which is descriptive qualitative in nature. This study uses an astronomical and syar'i approach. Source of data in this study from primary data and secondary data. Data processing techniques and data analysis in the form of data reduction, data presentation, inference, and verification as well as the final conclusion. The results of the study found that 5 out of the 13 mosques in this study still had an inaccurate Qibla or did not face the true Qibla. Qibla tracker and protractor methods get the same results as the google earth method. The implication of this research is that it is hoped that the local government, especially the KUA, will re-verify the Qibla direction of the mosque in order to correct the deviation that has occurred. In addition, it is necessary to socialize the accuracy of the Qibla direction to the community and provide a basic understanding to the community regarding the importance of the Qibla direction in carrying out worship, as well as the instruments used in determining the Qibla direction. Keywords : Accuracy, Qibla Direction, Mosque